On Some Criteria for Defining Lexical Semantics - Yerznkyan, Yelena; Harutyunyan, Lusine (Armenian Folia Anglistika, 2010)
The article examines the two major types of word meaning – broad meaning and polysemy. An attempt is made to define the standards which will make the distinction between these complicated, extremely indefinite and at times partly or fully coinciding phenomena possible. The research demonstrates that broad-meaning and polysemantic words differ from each other not only functionally and semantically, but also with their semantic structure which is the direct outcome of the historical process of the change of meanings. In case of broad meaning words, there are more meanings since the number of the denotators of the latter is not limited. Rather, it is predetermined by its theoretically possible subtexts whereas the number of the meanings of the polysemantic words is determined by the number of the denotators fixed by itself.